Bisakah Generasi Z Mengatasi Stres Teknologi? Peran Moderasi Pelatihan dan Efikasi Diri Kreatif - M. Usman Rosyid; Nury Ariani Wulansari (JURNAL MANAJEMEN MOTIVASI, 2026)
Digital transformation has increased technology use in the workplace but also intensified technostress, potentially reducing employee performance. This study examines the effect of technostress on job performance and the moderating roles of training and creative self-efficacy among Generation Z employees in Semarang. Using a quantitative survey of 200 respondents, data were analyzed with SEM-PLS. The findings reveal that technostress negatively affects job performance, while training weakens this negative effect. Creative self-efficacy does not significantly moderate the relationship. The results highlight the importance of continuous training to help organizations mitigate technostress and sustain employee performance in digital work environments.